2021
DOI: 10.7717/peerj.11857
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of yield components in spring wheat collection harvested under two water regimes in Northern Kazakhstan

Abstract: Background Bread wheat is the most important cereal in Kazakhstan, where it is grown on over 12 million hectares. One of the major constraints affecting wheat grain yield is drought due to the limited water supply. Hence, the development of drought-resistant cultivars is critical for ensuring food security in this country. Therefore, identifying quantitative trait loci (QTLs) associated with drought tolerance as an essential step in modern breeding activities, which rely on a marker-assisted sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The QTLs identified in this study were analyzed and compared with the QTLs previously reported for APR resistance to LR and SR that were identified using GWAS data from RIBSP 2018–2019 [ 33 ] and the QTLs previously reported to be associated with yield-related traits identified using GWAS data from northern Kazakhstan 2018–2020 [ 34 ] ( Table 4 ). In addition, the location of each identified QTL was compared to the genetic positions of known Lr and Sr genes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QTLs identified in this study were analyzed and compared with the QTLs previously reported for APR resistance to LR and SR that were identified using GWAS data from RIBSP 2018–2019 [ 33 ] and the QTLs previously reported to be associated with yield-related traits identified using GWAS data from northern Kazakhstan 2018–2020 [ 34 ] ( Table 4 ). In addition, the location of each identified QTL was compared to the genetic positions of known Lr and Sr genes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, all nine QTLs in this comparative assessment were characterized by similar directions of QTL effects, i.e., toward either resistance or susceptibility. In addition, five out of these nine QTLs were earlier found to be associated with yield components [ 34 ] ( Table 4 ), suggesting that these QTLs might directly influence the field performance of bread wheat. The comparative evaluation of all eleven identified QTLs suggests that two QTLs ( QLr.ipbb-1A.3 and QLr.ipbb-1B.5 ) were presumably novel, as they were not reported in previously published LR and SR studies ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the MP developed by using two genetically distinct parents bred in the UK and Russian Federation was genotyped based on 4,595 SNPs in all three subgenomes. The SNP genotyping of this MP provided higher resolution than in our latest QTL mapping effort using Avalon x Cadenza MP, which relied on 3,647 polymorphic SNPs ( Amalova et al, 2021a ). Moreover, whereas the Avalon x Cadenza doubled haploid MP was constructed using two British cultivars, the PAxP MP was developed using varietal representatives of two genetically distant pools that were tested in three wheat-growing regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The QTL analysis was performed using data from every year and location and the QTL identification was conducted as previously described in Amalova et al (2021a) and Amalova et al (2021a) . Specifically, the composite interval mapping (CIM) method of Windows-based QTL Cartographer v2.5 software ( Wang, Basten & Zeng, 2012 ), with the logarithm of the odds ratio (LOD) threshold of 3.0 was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation